Assessment of Electrolyte Abnormality in Acute Stroke Patients - Shaik Rabbani; N Sathish Reddy (Asian Journal of Medical Research, 2021)
Background: To determine electrolyte abnormality in acute stroke patients. Subjects and Methods: 102 patients of stroke of both genders were enrolled. All were subjected to assessment of electrolytes level. Results: Age group 30-40 years comprised of 12 patients, 40-50 years had 28, 50-60 years had 25 and >60 years had 47 patients. A significant difference was observed (P< 0.05). Type of stroke was hemorrhagic in 48 and ischaemic in 54 patients. A non- significant difference was observed (P> 0.05). Dyselectrolytaemia in haemorrhagic stroke patients was seen in 40% and in ischaemic stroke patients in 65%. The mean serum osmolality in haemorrhagic stroke patients was 292.1 mmol/kg and in ischaemic stroke was 306.4 mmol/kg, urine sodium was 62.4 mEq/L/24 hours in haemorrhagic stroke patients and 67.4 mEq/L/24 hours in ischaemic stroke patients and urinary potassium was 78.6 mEq/L/24 hours in haemorrhagic stroke patients and 74.8 mEq/L/24 in ischaemic stroke patients. The difference was non- significant (P> 0.05). Sodium level found to be normal in 24 patients, hyponatraemia in 56 and hypernatremia in 22 patients. The difference was significant (P< 0.05). Conclusion: Sodium level was altered with hyponatremia was seen in most of the patients. The level of electrolytes should be assessed in stroke patients. Maximum cases of ischemic stroke in age group >60 years was seen.